Kommentierte Beständeübersicht des Landesarchivs Schleswig-Holstein Bestandsaufnahme zum 150-jährigen Bestehen - Hering, Rainer (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2020)
This overview of holdings is an inventory to mark the 150th anniversary of the Landesarchiv Schleswig-Holstein, which was founded in 1870 as the Prussian Staatsarchiv Schleswig. This overview is the first printed overview that contains explanations of all individual holdings and thus facilitates orientation for the users of the Landesarchiv. Reading and leafing through the book, one can get an impression of the local records on regional history and discover many things that have not yet been researched. The book guides the reader through the extensive holdings in a compact and clear manner - if one were to put all the documents in one row, it would result in a distance of about fifty thousand linear metres.